PENGETAHUAN IBU BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN DIARE PADA ANAK USIA PRESCHOOL - Benedictus Aditya Permana Putra; Tuti Asrianti Utami (LPPM STIKES Muhammadiyah Kendal, 2020)
Diarrhea occurs due to abnormalities in digestive function, absorption, and secretion. Increasing the number of stools with increased water content is a result of changes in water and electrolyte transportation in the gastrointestinal system. The spread of infectious diseases such as diarrhea can be through the hands, especially in preschool children, so it is necessary to prevent diarrhea. This study uses a cross-sectional design, using a questionnaire. The sample of the study was 80 mothers who had preschool children. Statistical tests used by the Kendall test or know c. The results of this study indicate a relationship between maternal knowledge (p = 0,000 with diarrhea prevention behavior. Unrelated factors in this study were maternal age (p = 0.813), maternal education (p = 0.920), occupation (p = 0.686), researcher expectations is that mothers in Johar Baruvillage always have good knowledge to prevent diarrhea in their children.